2018
DOI: 10.1002/ejic.201800093
|View full text |Cite
|
Sign up to set email alerts
|

Design of Graphene Nanoplatelet/Graphitic Carbon Nitride Heterojunctions by Vacuum Tube with Enhanced Photocatalytic and Electrochemical Response

Abstract: The vacuum tube method has been used for the construction of nondestructive and physically stable graphitic carbon nitride/graphene nanoplatelet composites and their photocatalytic behavior studied by measuring different photoactivities, such as photocurrent, photoluminescence, and the photodegradation of tetracycline hydrochloride under visible‐light irradiation. The formation of a heterojunction was confirmed by XRD, TEM, SEM, FTIR, XPS, and Raman spectroscopy. The results of this research indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The red phosphorus/graphitic carbon nitride possess type-I heterojunction with enhanced catalytic behavior [ 26 ]. Tahir Muhmood et al used the vacuum tube method to construct nondestructive and physically stable graphitic carbon nitride/graphene nanoplatelet composites, which achieved the complete degradation of tetracycline hydrochloride [ 27 ]. It can be seen that the construction of heterojunction catalyst has the potential to improve the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The red phosphorus/graphitic carbon nitride possess type-I heterojunction with enhanced catalytic behavior [ 26 ]. Tahir Muhmood et al used the vacuum tube method to construct nondestructive and physically stable graphitic carbon nitride/graphene nanoplatelet composites, which achieved the complete degradation of tetracycline hydrochloride [ 27 ]. It can be seen that the construction of heterojunction catalyst has the potential to improve the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…To improve these deficiencies, researchers have regulated g-C 3 N 4 to enhance the photocatalytic properties [12,13]. For instance, Xia group reported graphitic carbon nitride/graphene nanoplatelets composites was prepared via a novel vacuum tube method to achieve a complete degradation of tetracycline hydrochloride under visible light irradiation due to the larger surface area and higher charge separation ability [14]. The spherical graphite carbon nitride was successfully prepared using a solvent thermal method by Muhmood et al which showed a wider visible light absorption and lower photoinduced charge carrier recombination than bulk g-C 3 N 4 , Tetracycline hydrochloride can be completely degraded within 110 min under the catalysis of the improved spherical C 3 N 4 [15].…”
Section: Introductionmentioning
confidence: 99%
“…E.g., graphene nanoplatelets bridge between two semiconductors (AgBr and graphitic carbon nitride) boost photoelectrochemical performance [ 18 ]. Effective photocatalysts generated the superoxide radical (O 2 − ) and holes (h + ) were used to achieve the complete degradation of tetracycline hydrochloride [ 19 ]. Graphene oxide-TiO 2 composite was used for the degradation and mineralization of two hazardous pollutants—diphenhydramine pharmaceutical and methyl orange azo dye—under both near-UV/Vis and visible light irradiation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%